TTC36 promotes proliferation and drug resistance in hepatocellular carcinoma cells by inhibiting c-Myc degradation - Fengling Shao; Runzhi Wang; Xinyi Li; Yanxia Hu; Zaikuan Zhang; Jing Cai; Jieru Yang; Xiaosong Feng; Suxia Ren; Zengyi Huang; Yajun Xie (Cell Death and Disease)
Abstract High c-Myc protein accumulation contributes to the proliferation, invasion, and drug resistance in multiple cancer cells, but the underlying mechanism about c-Myc accumulation remains not to be elucidated. Here, we demonstrate that TTC36 promotes c-Myc protein accumulation in hepatocellular carcinoma cells, thereby driving the proliferation and sorafenib resistance in hepatocellular carcinoma cells. Ttc36 depletion disrupts the interaction between SET and PPP2R1A, consequently activating PP2A. Activated PP2A directly dephosphorylates p-c-MycS62 and activates GSK3β, relying on AKT, leading increased phosphorylation of p-c-MycT58, finally promotes FBXW7-mediated polyubiquitination and degradation of c-Myc. Inhibitors targeting GSK3β and PP2A effectively reverse the sorafenib resistance promoted by TTC36. These findings highlight the crucial role of TTC36 in c-Myc accumulation-caused proliferation and sorafenib resistance in HCC, providing a promising combination strategy for treating patients with c-Myc protein accumulation in advanced HCC.